PRINSIP KEDAULATAN RAKYAT SEBAGAI LANDASAN UJI KONSTITUSIONALITAS DALAM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 176/PUU-XXII/2024 : Popular Sovereignty as the Foundation for Constitutional Review in the Constitutional Court Decision Number 176/PUU-XXII/2024 - Alivio Rizqi Priambodo; Ali Rido (Faculty of Law, Universitas Trisakti, 2026)
The principle of popular sovereignty is the normative basis for the implementation of constitutional review of laws in Indonesia. In this regard, the Constitutional Court (MK) has a strategic role in ensuring that every piece of legislation is in line with the will of the people as mandated by the 1945 Constitution. The research question is: how does the MK position the principle of popular sovereignty as a basis for legal considerations in MK Decision Number 176/PUU-XXII/2024 and what are the implications for the practice of constitutional review? This research uses a normative legal research method, is descriptive in nature, uses secondary data obtained through literature studies, analyses data qualitatively, and draws conclusions deductively. The results of the study and conclusions show that the Constitutional Court not only conducts textual testing of norms against the 1945 Constitution, but also prioritises interpretations based on substantive democratic values, particularly in the protection of political rights and people's representation. This approach strengthens the function of judicial review as an instrument for safeguarding people's sovereignty, but at the same time raises debates about the limits of the judicial role and legislative authority.